Intrinsic magnetic field sensitivity in coinage transition metal-based nanostructures (Ag, Au and Cu) - Nurul Akmal, Che Lah (Elsevier Ltd, 2025)
The magnetic properties of coinage metal nanostructures (Ag, Au, Cu) are profoundly influenced by magnetic interactions within nanohybrids or nanocomposites. These interactions, particularly magnetic dipolar interactions at interfaces, lead to deviations from diamagnetic to paramagnetic or ferromagnetic behaviour. The key to achieving this condition lies in the relativistic interaction between an electron's orbital motion and its spin. Despite this, the characteristics of orbital angular momentum (OAM) in coinage nanostructures remain underexplored. This review elucidates the mechanism of OAM at the interface of coinage nanostructures, based on sp orbital hybridisation, which ultimately leads to the electric polarisation of surface states even in the absence of spin-orbit coupling. These discoveries have catalysed the rise of a rapidly expanding field of orbitronics, which leverages OAM to manipulate magnetic device-based coinage nanostructures. Additionally, recent developments in fundamental orbitronics and their implications for related behaviours are reviewed. Lastly, the future avenues of research concerning magnetically influenced OAM are outlined.